Validation of a selection battery used by the South African Military Academy - Pretorius, Marlize; Redelinghuys, Marlize (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.